2014
DOI: 10.1179/1879139514y.0000000165
|View full text |Cite
|
Sign up to set email alerts
|

Influence of charge segregation on specific aluminium consumption in production of ferro-titanium

Abstract: Specific aluminium consumption in the production of ferro-titanium through alumino-thermic reduction is usually far above the stoichiometric requirement, in industrial processes. A thermochemical analysis of the process in an industrial operation was carried out to explore this phenomenon. Aluminium was lost as volatile oxides. Entrapment of titanium in the slag layer led to lower recoveries and higher specific aluminium consumption. Oxidation of aluminium by atmospheric oxidation contributed to an increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…Chumarev et al evaluated the production efficiency of the FeTi alloy according to the components of ilmenite (FeTiO 3 ) [2]. Misra et al evaluated the recovery efficiency of Ti metals and the consumption of the reducing agent, Al, according to the volume of slag used [23]. However, the thermodynamic calculation of optimum mixing conditions according to the amounts of the compounds used has not been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Chumarev et al evaluated the production efficiency of the FeTi alloy according to the components of ilmenite (FeTiO 3 ) [2]. Misra et al evaluated the recovery efficiency of Ti metals and the consumption of the reducing agent, Al, according to the volume of slag used [23]. However, the thermodynamic calculation of optimum mixing conditions according to the amounts of the compounds used has not been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in Al and KClO 4 contents increased material loss caused by sputtering and decreased the yield of target material to ingot, when the Al and KClO 4 contents exceeded 20 mass% and 7 mass%, respectively. It was also reported that an increase of slag volume was detrimental to the recovery of titanium and increased consumption of aluminum [24]. Thus, reducing the slag volume is considered a target for future improved production of ferrotitanium.…”
Section: Introductionmentioning
confidence: 99%